Respuesta :

Step-by-step explanation:

Given:

  • [tex]y = 2x - 2[/tex]

Substitute the given value for y into the first equation:

[tex]4x - (2x - 2) = 10[/tex]

Use Distributive Property with negative sign:

[tex]4x - 2x + 2 = 10[/tex]

Subtract:

[tex]2x + 2 = 10[/tex]

Subtract 2 from both sides:

[tex]2x = 8[/tex]

Divide both sides by 2:

[tex]x = 4[/tex]

Substitute x = 4 into the second equation:

[tex]y = 2(4) - 2[/tex]

Solve:

[tex]y = 6[/tex]

Check:

[tex]4(4) - 6 = 10[/tex]

[tex]16 - 6 = 10[/tex]

Correct.

[tex]6 = 2(4) - 2[/tex]

[tex]6 = 6[/tex]

Correct.

x = 4

y = 6

As an ordered pair:

(4, 6)

ACCESS MORE